Temporal Change in Atmospheric Radiocesium during the First Seven Years after the Fukushima Dai-ich Nuclear Power Plant Accident - Tomohisa Abe; Kazuya Yoshimura; Yukihisa Sanada (Aerosol and Air Quality Research)
Abstract After the Fukushima Daiichi Nuclear Power Plant accident, the Nuclear Regulation Authority monitored the atmospheric radiocesium concentration as a national project to assess its temporal changes from August 2011 till November 2017. The concentration ranged from 10−1 to 100 Bq m−3 during the first two years but from 10−5 to 10−1 Bq m−3 approximately seven years following the accident. Additionally, the resuspension factor (RF) fell between 10−7 and 10−6 m−1 at the beginning of the third year but eventually declined to values between 10−11 and 10−7 m−1. To investigate the effect of anthropogenic activities on the temporal change in this parameter, we categorized the monitoring data into those from within and without the entry-restricted zone. The latter exhibited a higher rate of decrease in the RF, which agrees with the previously reported data on the time dependence of the air dose rate and suggests that anthropogenic activities promote environmental remediation and reduce atmospheric radiocesium. Finally, as the rate observed in this study exceeds that reported for the Chernobyl Nuclear Power Plant accident over the corresponding period, it warrants ongoing assessment based on current monitoring data.